UNEXPECTED ISOLATED HYPOPHOSPHATEMIC RICKETS ASSOCIATED WITH ELEMENTAL FORMULA FEEDING - Teoh, Sze Teik; Leong, Annie; Idris, Arini Nuran; Lim, Poi Goik (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Phosphate deficiency is common in rickets but is accompanied by calcium or vitamin D deficiency (also named nutritional rickets). Isolated hypophosphatemic rickets (HR) without hypovitaminosis or defective renal phosphate handling is uncommon. Phosphate is abundant in diet and its GI absorption even though primarily mediated by vitamin D, is less tightly regulated with about 30% being passive. Recently, there has been an increase in such HR cases reported associated with the use of elemental formula (EF). RESULTS The patient was born prematurely at 31 weeks and diagnosed having Tetralogy-of-Fallot (TOF) with severe pulmonary stenosis requiring Blalock-Taussig (BT) shunt at 3-month-old. Postoperatively, he had heart failure and gastroesophageal-reflux-disease (GERD), for which he was treated with heart failure drugs (furosemide, spironolactone, captopril) and antireflux (omeprazole, domperidone), respectively. At 2-months-old, he was diagnosed with Cow’s Milk Protein Allergy (CMPA) and EF was commenced. Both Neocate® and Comidagen® were used interchangeably. He developed rickets at 8-month-old with initial serum phosphate 0.5mmol/L, calcium 2.46mmol/L, ALP 1432 IU/L, and 25(OH)- Vitamin D 80 nmol/L (sufficient). His urine TRP was normal and radiological findings were consistent with rickets. Notably, he developed acute severe hypocalcemia with hyperphosphatemia, immediately following oral Sandoz phosphate, despite calcium supplementation. His subsequent response, however, was partial and the hypophosphatemia persisted. He was switched to soy-based formula at 10-months-old, with ensuing improvement in serum phosphate. He achieved biochemical and radiological healing of rickets within 3 months of follow-up. CONCLUSION HR in certain infants relating to the prolonged and sole use of EF had been reported elsewhere with its etiology not fully understood but could relate to the reduced bioavailability of phosphate in EF. Replacement with an alternative phosphate form could cause transient acute severe hypocalcemia and hyperphosphatemia possibly due to sudden upregulation of Na-Pi2b cotransporter in the gut after phosphate starvation. The cessation of EF reverses the pathology.